An expandable thermoelectric power generator and the experimental studies on power output. (October 2020) - Li, Kewen; Garrison, Geoffrey; Moore, Michael; Zhu, Yuhao; Liu, Changwei; Horne, Roland; Petty, Susan
Highlights: A Novel five-layer thermoelectric generator (TEG) device was designed and built. The expandability of the TEG device provides a possible solution to scaling up to commercial size power. The voltage and power increase with temperature difference almost linearly. The efficiency of TEG increases with water flow rate on the cold side but decreases with the increase in water flow rate on the hot side. The voltage, power output, and efficiency of each layer is almost the same, which makes the delivering of electricity more uniform and more stable. Abstract: Technology using thermoelectric generators (TEG) has many advantages such as compactness, quietness, and reliability because there are no moving parts. One of the great challenges for TEG to be used for power generation is large-scale utilization. It is difficult to manufacture a TEGS system even at the scale of a few kilowatts (kW). To this end, we have designed and built a five-layer TEG apparatus with 90 individual power-producing TEG modules that can be installed with modularized units. Such a system with a layered structure could be expanded in power, something similar to solar Photovoltaics (PV). In this study, laboratory experiments were conducted using the built TEG apparatus to measure the power output and efficiency at different flow rates of water, different temperature, and different temperature differences between hot and cold sides. The effects of these parameters on voltage, power output, and efficiency were investigated and analyzed. The five-layer TEG device could generate about 45.7 W electricity with a temperature difference of 72.2°C between the cold and hot sides. The power of each module was about 0.51 W at this temperature difference. The experimental data can be applied to the design of commercial TEG systems. The expandable TEG system with layered structure provides a possible solution to scaling up TEG power generation to a commercial size.